2019
DOI: 10.1002/er.4773
|View full text |Cite
|
Sign up to set email alerts
|

Study on design and thermal characteristics of vacuum tube solar collector intubated with heat storage tube

Abstract: Summary In this work, a heat storage vacuum tube solar collector intubated with heat storage tube is designed, which consists of solar vacuum tube, phase change material insert tube, and heat holding cover. The internal energy conversion, transmission, and storage theory are established based on the structure of the heat storage vacuum tube. The parallel and series‐parallel solar air collector system prototype consisting of nine heat storage solar vacuum tube solar collectors is designed and tested. The test r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…At the same operating temperature, the methanol conversion rate of the indirect heating reactor is higher than that of an electric furnace reactor. Yongtai et al (2019) [13] studied the thermal characteristics of the heat storage tube and vacuum tube solar collector. Based on the structure of the heat storage vacuum tube, the internal energy conversion, transmission, and storage theories are formed.…”
Section: Design Optimization Of Electronic Heat Absorption Equipment ...mentioning
confidence: 99%
“…At the same operating temperature, the methanol conversion rate of the indirect heating reactor is higher than that of an electric furnace reactor. Yongtai et al (2019) [13] studied the thermal characteristics of the heat storage tube and vacuum tube solar collector. Based on the structure of the heat storage vacuum tube, the internal energy conversion, transmission, and storage theories are formed.…”
Section: Design Optimization Of Electronic Heat Absorption Equipment ...mentioning
confidence: 99%
“…The other type is a U-tube ETSC, which is the same concept, except that the heat pipe is changed to a copper tube that goes into the evacuated tube and comes back to the header again so that it has an inlet header and an outlet header. 19…”
Section: Evacuated Tube Collectormentioning
confidence: 99%
“…All the heat pipes are connected to the header which allows the heat to be transformed from the heat pipes to the fluid inside the tank. The other type is a U ‐tube ETSC, which is the same concept, except that the heat pipe is changed to a copper tube that goes into the evacuated tube and comes back to the header again so that it has an inlet header and an outlet header 19 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many researchers are interested in studying the phase change materials (PCM) and using them with solar heaters in order to store heat for a longer time. In solar air heaters integrated with PCM, many researchers have experimented the effect of using acetamide (Mehla and Yadav 2018 ), paraffin (Abokersh et al 2017 ; Algarni et al 2020 ; Essa et al 2018 ; Z. Wang et al 2020 ), and other materials such as stearic acid, mannitol-graphite, and erythritol (Chopra et al 2019 ; Li and Zhai 2017 ; Yongtai et al 2019 ). All found that PCM increases the efficiency of thermal performance and thermal storage, where the heat lasts longer after the disappearance of sunlight.…”
Section: Introductionmentioning
confidence: 99%